2007
DOI: 10.1542/peds.2006-1878
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Effectiveness Against Medically Attended, Laboratory-Confirmed Influenza Among Children Aged 6 to 59 Months, 2003–2004

Abstract: Full vaccination provided measurable protection against laboratory-confirmed influenza among children who were aged 6 to 59 months during a season with suboptimal vaccine match. No vaccine effectiveness was identified with partial vaccination among children who were aged 6 to 23 months, affirming that children need to be fully vaccinated to obtain protective effects. These results strengthen the evidence of the vaccine's ability to reduce substantially the burden of disease in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(59 citation statements)
references
References 28 publications
1
56
0
2
Order By: Relevance
“…[153,156,157] Several observational studies of TIV VE among children less than 5 years of age have found a VE of 60-85% in seasons where vaccine strains are well-matched to circulating strains, but a VE of 0-60% when vaccines are poorly matched to circulating strains. [158][159][160][161][162][163][164] In addition to the direct protection of children conferred by influenza immunization, limited data indicate that protection of unvaccinated household [165,166] and community contacts [154] may be conferred by immunization of children.…”
Section: Inactivated Influenza Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…[153,156,157] Several observational studies of TIV VE among children less than 5 years of age have found a VE of 60-85% in seasons where vaccine strains are well-matched to circulating strains, but a VE of 0-60% when vaccines are poorly matched to circulating strains. [158][159][160][161][162][163][164] In addition to the direct protection of children conferred by influenza immunization, limited data indicate that protection of unvaccinated household [165,166] and community contacts [154] may be conferred by immunization of children.…”
Section: Inactivated Influenza Vaccinesmentioning
confidence: 99%
“…[167][168][169] Observational studies have demonstrated that children who had not previously received vaccine and who received only one dose of vaccine had no statistically significant protection while children who received two doses had significant protection. [159,163,170,171] As a result of these data, all children aged 6 months to 8 years who are being vaccinated for the first time should receive 2 vaccine doses separated by ≥4 weeks. Once a child has been primed, either with vaccine or natural infection, a single dose of vaccine should elicit protective antibodies.…”
Section: Inactivated Influenza Vaccinesmentioning
confidence: 99%
“…The recent CDC influenza vaccination recommendations extended protection to the entire population after the pandemic first wave to reduce overall influenza infection rates 11 .…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…The few published studies that have evaluated influenza vaccine in children less than 24 months of age have estimated the vaccine efficacy/effectiveness to range from -7% up to 52%, depending on a variety of factors including the outcome measured, the particular influenza season, and the number of vaccine doses. 16,17 In contrast, studies of the effectiveness of influenza vaccination among older children premature birth and low birth weight, routine infant immunization status and influenza vaccination status. Overall, asthma or reactive airway disease (documented on at least two separate occasions) accounted for 41% of chronic illnesses.…”
Section: Introductionmentioning
confidence: 99%